Gonad Maturity Rate of Gray Eeltailed Catfish with Different hCG Induction - Tri Yulianto; Wiwin Kusuma Atmaja Putra; Shavika Miranti; Tri Hardiyanti; Syarifah Fitriana; Fauzanadi Fauzanadi (Jurnal Perikanan dan Kelautan, 2019)
Gray eeltailed catfish is one of the local commodities in the Riau Islands. Domestication and aquaculture has not been done. Reproduction is one of problems in the Aquaculture effort. Gonadal maturity is stage preparation of the prospective parent for spawning process. One of efforts to gonad maturation is hormonal induction. This study purpose to determine effect of various brands hCG hormones on gonad maturity and determine the best hCG hormone brands that can accelerate the maturity of gonad fish crossing optimally. The research design was a completely randomized design with 5 treatments (hCG Polaris hormone, hCG sifation, hCG Chorullon, Oodev and NaCl solvent with 3 replications. The best hCG hormone is the hCG Polaris hormone reaching gonad maturation II. The best Treatment were the Oodev hormone treatment (gonadosomatic index (0.54 ± 0.19%), gonadal maturity level (gonad 3), egg diameter (0.54 ± 0.19 mm)